2x + y = 20
6x - 5y = 20
2x + y = 20
Subtract 2x on both sides to get "y" by itself, so you can later substitute it into the second equation.
2x + y - 2x = 20 - 2x
y = 20 - 2x
6x - 5y = 12
6x - 5(20 - 2x) = 12 Multiply 5 into (20 - 2x)
6x - 100 + 10x = 12 Combine like terms
16x - 100 = 12 Add 100 on both sides
16x - 100 + 100 = 12 + 100
16x = 112 Divide 16 on both sides to get "x" by itself
x = 7
Plug in x into either of the original equations to find y.
2x + y = 20
2(7) + y = 20
14 + y = 20
y = 6
x = 7, y = 6